ACCOUNTING FOR GOVERNMENT PERFORMANCE IN THE DEVELOPMENT OF THE NIGER DELTA REGION OF NIGERIA - Idamoyibo, Hwerien Rosemary (The International Journal of Accounting and Business Society, 2020)
Purpose: This paper accounts for Government performance in the development of the Niger Delta Region of Nigeria. The aim is to investigate the impact of government performance on school enrolment figure and state governments’ expenditures on health on the human development index of the region from the period, 1990-2018.Design/Methodology/Approach: The paper adopted the ex-post facto research design and made use of secondary data obtained from the Central Bank of Nigeria Statistical Bulletin and the World Bank Data. The population of the Niger Delta comprises forty million, six hundred and forty-five thousand, two hundred and five (40,645, 205) individuals in the region. The data obtained was statistically analysed using multiple linear regression. The Statistical Package for Social Science (SPSS) version 22 was employed for the analysis of the study.Findings: The study found that with the huge revenue generated from crude oil and natural gas by the Nigerian Government from the Niger Delta region, the school enrolment figure and state governments’ expenditures on health do not have an impact on human development index on the development of the Niger Delta Region.Unique contribution to theory, practice and policy: This study has contributed to the body of knowledge through Accounting for government performance and development of the Niger Delta region of Nigeria, using human development index, school enrolment figure and State governments’ expenditure on health as variables. The study recommends that Ministry of education, health and the State governments must work hard, in order to achieve the Sustainable Development Goals (SDG) in the education and health sector. The education and health budgetary allocations must be taken seriously and monitored thoroughly so as to ensure every kobo is accounted for. Maximum impact must be felt from whatever the government sets aside as the education and health budget and this could be seen to also improve the human capital development in the region. Finally, the State governments should also collaborate with the communities to implement good healthcare system and also quality education in the Niger Delta. The essence of this is not just to stop at the budgeting, but also to ensure full and accountable implementation of the health and education budget.Keywords: Nigeria Economy, Accounting, Government Performance, Development, Niger Delta Region.